CNT/PDMS composite membranes for H2 and CH4 gas separation - Nour, Majid; Berean, Kyle; Balendhran, Sivacarendran; Ou, Jian Zhen; Du Plessis, Johan; McSweeney, Chris; Bhaskaran, Madhu; Sriram, Sharath; Kalantar-zadeh, Kourosh (International journal of hydrogen energy, 2013)
Polydimethylsiloxane (PDMS) composites with different weight amounts of multi-walled carbon nanotubes (MWCNT) were synthesised as membranes to evaluate their gas separation properties. The selectivity of the membranes was investigated for the separation of H2 from CH4 gas species. Membranes with MWCNT concentrations of 1% increased the selectivity to H2 gas by 94.8%. Furthermore, CH4 permeation was almost totally blocked through membranes with MWCNT concentrations greater than 5%. Vibrational spectroscopy and X-ray photoelectron spectroscopy techniques revealed that upon the incorporation of MWCNT a decrease in the number of available Si–CH3 and Si–O bonds as well as an increase in the formation of Si–C bonds occurred that initiated the reduction in CH4 permeation. As a result, the developed membranes can be an efficient and low cost solution for separating H2 from larger gas molecules such as CH4. •PDMS nanocomposite membranes of different MWCNT concentrations were synthesized.•The membranes were investigated for separating H2 and CH4 gas molecules.•Si–CH3, Si–O, and Si–C bonds played important roles in the membranes' performance.•More than 1wt% of MWCNT in membranes selectively attenuated the permeation of CH4.•MWCNT emerged as an effective additive for tuning H2/CH4 membranes' selectivity.